Outcome of twin pregnancies conceived after assisted reproductive techniques - A Baxi; M Kaushal (Wolters Kluwer Medknow Publications, 2008)
Context : There is a continuous controversy regarding the obstetric perinatal outcome of twin pregnancies conceived after assisted reproductive techniques (ART). There is an ongoing discussion whether theses parameters may show poorer results as compared to spontaneous conception. Aims: To evaluate the outcome of multifetal pregnancies and to compare maternal and neonatal complications between spontaneously conceived and assisted reproductive therapy. Settings and Design : Prospective case-control study. Materials and Methods :In this prospective case-control study of 2-year duration, obstetric and perinatal outcomes were compared in 36 ART twin pregnancies (Group A) with 138 twins who conceived naturally (Group B). The outcomes were analyzed and used for a comparison between spontaneous and assisted multifetal pregnancies. Statistical Analysis : The continuous variables were analyzed by Student's t -test and categorical variables were analyzed with Fisher's exact test. Results : Pregnancy-related complications like pregnancy-induced hypertension, antepartum hemorrhage, were similar in both groups. Incidence of cesarean section, preterm delivery, and hospital stay was significantly more in Group A vs. Group B, P < 0.001. The newborns in the assisted group had more complications than the spontaneous group; most notable were respiratory distress syndrome, newborn intensive care admission, sepsis, and longer hospital stay (4.8 days vs. 1.6 days, P < 0.001). Conclusions : Increased rates of cesarean section and preterm delivery are the main reasons for increased obstetric risk in pregnancies conceived through ART. Preterm birth and neonatal prematurity-related complications were the main cause for longer stay in hospital in ART-conceived twins.